Medicinal properties of Plantago major: hypoglycaemic and male fertility studies - Noor, Hamdan; Juing, M.; Chee, Beng Jin; Kueh, B. L.; Othman, Zolkepli (Universiti Putra Malaysia Press, 2000)
Plantago major extract has been traditionally used for treating diabetes and to increase male fertility. This study was conducted to verify its efficacy. The hypoglycaemic property of P. major aqueous leaf extract was determined 1Yy oral administration of four treatment doses (l00, 200, 400 and 600 mg/kg body weight). Saline and glibenclamide were used as controls. Glucose Tolerance Test was done at -10, 0, 5, 15, 30, 60, 90, 120 and 180 minutes and the plasma glucose concentration was determined 1Yy the glucose oxidase assay. The study showed that only the 600 mg/kg dose had a significant effect in reducing blood glucose level in diabetic rats. However, the effect of the aqueous extracts was less pronounced compared to glibenclamide. In the fertility study, an aqueous extract from P. major seeds was given orally to rats at 30, 60, 100 and 200 mg/kg body weight respectively. The effect of each dose on vas deferens sperm concentrations after 20 days of treatment was determined. Analysis of the data showed significant increases in sperm concentrations in the 60, 100 and 200 mg/kg body weight groups. However, the trend in increased testosterone levels from day 8 to 14 in the 60 and 200 mg/kg groups was insignificant, suggestive of other factors, possibly antiestrogens in the seed extract contributing to the spermatogenic effect. The studies suggest that aqueous extract from P. major could contain chemicals for treating diabetes mellitus and male infertility problems.